Eating fractions - McMillan, Bruce (New York : Scholastic, 1991)
Food is cut into halves, quarters, and thirds to illustrate how parts make a whole. Simple recipes included.
Children's Catalog (Wilson)
Publisher's Weekly
*SLJ*
1.7
K-3
Keywords: Fractions -- Juvenile literature; Fractions; Cookery; Fractions; Cookery